IDENTIFIKASI MISKONSEPSI MATERI IPA KELAS VII SMP N 1 GUNUNG SUGIH LAMPUNG TENGAH - Ita Reziana; arwin achamad; rini rita t.marpaung (Universitas Lampung, 2017)
The purpose of the research was to know the misconception of Biology. The design of the research was descriptive. Research sample VIII grade students of SMPN 1 Gunung Sugih of Lampung Teng was choosed 50% of 123 student by random sampling. This research data were qualitative data and quantitative data. The qualitative data were obtained from science biology teachers interview result about misconception of Biology, while quantitative data was obtained from multple choice test and argumentation essay then analyesed used Certainty of Response Index (CRI) method. The calculation of misconception and dontknow concept reach 45% students. Score misconception was based on criteria CRI answers obtained from average value that was 19.16 15,66. The percentage of students that was 15.57% of misconceptions that was low criteria. The material that had the most dominant misconception was material